Pure or ambidextrous strategy? A study of responsive and proactive market orientations in industrial firms. Issue 6 (26th February 2020) - Wang, Yejing; Zhang, Haili; Song, Michael
Abstract : Purpose: The purpose of this study is to investigate the environmental conditions (i.e. competitive intensity) under which a pure strategy or an ambidextrous strategy of implementing responsive market orientations (RMOs) and/or proactive market orientations (PMOs) is more advantageous for firm's performance. Design/methodology/approach: Drawing upon the market orientation (MO) and strategy literatures, the authors test the study's model empirically using a sample of 308 US-based firms operating in industrial markets. All measurement items are taken from the widely used maturity scale which has been confirmed in the literature. Findings: The empirical results suggest that when the competitive intensity is high, pursuing a purity strategy of RMO while decreasing PMO is the best course of action. On the other hand, balancing between RMO and PMO (implementing a strategy of ambidexterity) can increase firm's performance in a low competitive intensity environment. Research limitations/implications: This study aims to contribute to the existing MO literature in several ways: first, this study advances the MO literature by emphasizing the moderating role of competitive intensity on the effects of different MO strategies (purity or ambidextrous MO strategy); second, this study focuses on the firms operating in industrial markets and informs managers on how to adopt RMO and PMO under different level of competitive intensity; third, this study is the extended research of the prior study published in this journal (Wang et al., 2013), which examined the environmental antecedents of adopting RMO and PMO. Practical implications: First, firms operating in industrial markets should increase RMO, while at the same time decrease PMO, in a highly competitive intensity environment. Second, companies should pursue both RMO and PMO at the same time in a low competitive intensity environment. Balancing between RMO and PMO can improve firms' performance in a low competitive intensity environment. Originality/value: This study contributes to the industrial business and marketing literature by sharpening the theoretical understanding of the impact of RMOs and PMOs on firm's performance. It also offers practical insights to managers of industrial firms on when to adopt RMOs and/or PMOs under different levels of competitive intensity.